Histogram Based Image Enhancement Techniques: A Survey - Gupta, P; Kumare, JS; Singh, UP; Singh, RK (International Journal of Computer Sciences and Engineering, 2025)
Image enhancement is a digital processing technique which does its best to get a better image. It is a simple and most engaging range in image processing. Image enhancement is a process by which we got an improved and high-quality image through the low contrast and low-quality image. Image Contrast enhancement without disturbing other parameters of the image is one of the difficult tasks in image. This paper focused on several enhancement techniques that deal with contrast of image. Image enhancement dealt with improvement in the appearance and quality of the given image without losing the information of the image. This paper includes several approaches of image enhancement these approaches are used for improving the given image which incorporates manipulation of gray scale, Histogram Equalization (HE) and Filtering. HE is the basic method of image enhancement. All the techniques presented by this study is simulated on Intel I3 64 bit processor using MATLAB R2013b. For quality measurement of contrast enhanced image Peak to signal noise ratio and Mean Square Error parameter for each of the methods is additionally computed.